The Secret Language of Birthdays: Personology Profiles for Each Day of the Year - Goldschneider, Gary; Editor Goldschneider, Aron (New York Vinking Books, 1994)
Offering a two-page spread on every day of the year, a one-of-a-kind combination of astrology and numerology presents an abundance of information, including personality profiles, illustrations, meditation suggestions, and more for each day. 20,000 first printing.
Includes Colored Ilustrarions and Index
Keywords: Astrology and psychology